Kegalauan Identitas: Dilema Hubungan Muslimin dan Hindu di Bali - Siti Raudhatul Jannah (Universitas Islam Negeri Mataram, 2012)
The relationship between Hindu and Muslim communities in Bali has been recorded in the long trajectory of history of both communities. As a human relationship, the relationship sometimes becomes strength, but at the other hand, as the adherents of different religions, it becomes challenge to them. The challenge is how the Muslim community in Bali can respect and honor Hindu religious traditions, and how the Hindu community can do the same to the Muslim community. The article aims to elaborate further about it. The author presents three cases as examples of how Muslims practice their religion in Bali context. Tolerance is the key word how to mingle in the social, moral principles, religious law and social ethics.